Value contribution of leniolisib in the Treatment of Activated PI3Kδ syndrome (APDS) in Spain using Multi-Criteria Decision Analysis (MCDA) - María Reyes Abad; Carmen Alerany; Luis Ignacio Gonzalez; Olaf Neth; Concepción Payares-Herrera; Carlos Rodríguez-Gallego; Jose Luis Trillo; Kirsten H. Herrmann; Raquel Figueiredo; Alicia Gil (Global & Regional Health Technology Assessment)
Background: Activated phosphoinositide 3-kinase (PI3K) δ Syndrome (APDS) is an ultra-rare, potentially life-threatening disease that lacks approved treatments in Spain. This study aimed to apply Multi-Criteria Decision Analysis (MCDA) to assess the value of the first pharmacological treatment for APDS in Spain.